A time-course evaluation of inflammatory and oxidative markers following high-intensity exercise in horses: a pilot study - MacNicol, J. L.; Lindinger, M. I.; Pearson, W. (Journal of Applied Physiology, 2018)
Exercise is a physiological stress resulting in reactive oxygen species and inflammatory mediators, the accumulation of which are thought to contribute to degenerative articular diseases. The horse is of particular interest in this regard as equine athletes are frequently exposed to repetitive bouts of high-intensity exercise. The purpose of this study was to provide a detailed description of the response of articular and systemic oxidative and inflammatory biomarkers following high-intensity, exhaustive exercise in horses. A group of horses (Ex) underwent repeated bouts of high-intensity exercise, at a target heart rate of 180 beats/min, until voluntary exhaustion. Baseline plasma and synovial fluid (SF) samples were taken 24 h before exercise and then at 0.5, 1, 2, 4, 8, and 24 h following exercise cessation. This time course was repeated in a group of nonexercised control horses (Co). Plasma and SF samples were analyzed for prostaglandin E2 (PGE2), nitric oxide (NO), total antioxidant status (TAS), and glycosaminoglycans (GAG). The Ex group had significantly higher plasma NO at 0.5, 1, and 2 h; and higher plasma PGE2 at 0.5 and 1 h compared with Co. SF PGE2 and GAG were also higher in Ex horses at 8 h compared with Co. It is concluded that high-intensity exercise in horses results in a rapid increase in systemic oxidative and inflammatory markers from 0.5 to 2 h after exercise, which is followed by local articular inflammation and cartilage turnover at 8 h postexercise. NEW & NOTEWORTHY In horses, the influence of exercise systemically and within the articular space remains unclear and requires further detailed characterization. In this study, we identify that an acute bout of high-intensity exercise in horses induces systemic inflammation and oxidative stress within 30 min of exercise cessation, which lasts for ~2 h. Articular inflammation and cartilage turnover were also be observed within the equine carpal joint 8 h following exercise completion.